Rating anthropometric parameters of children with polyarticular hypermobility - Cardinali, Mario; Weber-Nowakowska, Katarzyna (Journal of Education, Health and Sport, 2018)
Introduction: Polyarticular hypermobility manifests in an increased range of motion in the joints compared to standards that include gender and age. It is given that it occurs even in 30% of children. It can lead to many biomechanical disorders and injuries. Science, which describes the measurement of the different body parameters such as height, body weight or fat content in the body is anthropometry and it was used to characterize the child diagnosed with arthritis polyarticular hypermobility. Material and Methods: The study was conducted on the group of 35 children aged 6 to 11 years old with diagnosed polyarticular hypermobility. The control group were randomly selected children in the same age from the same school without diagnosed polyarticular hypermobility. Anthropometric parameters of all children were measured according to accepted methods. The children were tested for body weight, height, body mass index, WHR index and their skinfolds were measured by skinfolds calipers. Objective: The aim of this study was to evaluate the anthropometric parameters of children with diagnosed polyarticular hypermobility and to compare these results to their contemporaries with no identified polyarticular hypermobility. Results: All the examined parameters (height, body weight, BMI, WHR, skinfolds measurement) in the two groups were on very similar levels, there were no statistically significant differences (BMI p = 0.3435, WHR p = 0.806). Conclusions: There is no significant difference between the study group and the control group in the examined anthropometric parameters (height, body weight and BMI). Children with diagnosed polyarticular hypermobility in terms of weight and height do not stand out from their peers.